Evaluación económica de la producción y comercialización de carne de cerdo en San José de Aguas Negras del cantón Marcabelí - Ruiz Cárdenas, Sandy Gabriela (2023)
The imperative undertaking of an economic and productive inquiry is indispensable for scrutinizing the viability of a product, delineating the relevance of the investment, and elucidating the intricate processes to be executed within a specified temporal domain. In this investigative endeavor, the primary objective rested upon effectuating an economic evaluation germane to the production and commercialization of porcine commodities within the agrarian precincts of the San José de Aguas Negras locale in the Marcabelí Canton. This entailed an exhaustive diagnostic examination of the extant scenario, meticulous determination of economic indicators, and the formulation of a judicious proposition aimed at enhancing the operational facets of this undertaking. Methodologically, a descriptive approach was deployed, instrumental in delineating the salient variables earmarked for investigation. The modality of inquiry was executed through the strategic utilization of a survey coupled with an observation sheet, meticulously structured to encapsulate inquiries germane to both production and meat marketing. The ensuing trove of information was subjected to a systematic organization, tabulation, and subsequent interpretation. Upon culmination, a discernment surfaced affirming the lucrativeness of the production and marketing ventures. Nevertheless, a discerning scrutiny exposed inherent limitations within this sphere. Particularly, the state of infrastructure categorized 70% of the pigsties within the medium stratum, thereby prompting a judicious recommendation for the articulation of a comprehensive plan delineating the production and marketing paradigms specific to pork within the San José de Aguas Negras precinct of the Marcabelí Canton. This proposed plan, once implemented, is envisaged to empower local porcine agriculturists to refine their production processes, thereby ensuring the concomitant augmentation of meat quality and the optimization of production conditions for enhanced profitability.